Combining ideal types of performance and performance regimes: An integrated framework of analysis of performance management systems for public organizations. Issue 7 (3rd October 2019) - Giacomelli, Giorgio; Annesi, Nora; Barsanti, Sara; Battaglia, Massimo
Abstract : Purpose: The purpose of this paper is to contribute to the scholarship on public management models and to advance the theoretical conceptualization of the complexity of performance management systems (PMSs). The paper explores how the characteristics of PMSs vary within and across different organizational units in common institutional context, based on the case of a regional authority in Italy. Design/methodology/approach: A framework of analysis considering both objective and subjective factors was derived from a combination of performance typologies in the public sector, namely ideal types of managing performance (Bouckaert and Halligan, 2007) and performance regimes (Jakobsen et al., 2017). The combination of the characteristics of these two models across different Directorates General (DGs) has also been explored through a nested case study (Starman, 2013). Data were gathered via a desk analysis of official documents regarding the planning and programming of a regional authority along with in-depth interviews with top-level managers. Findings: The results highlighted a clear differentiation of PMSs, both within and across DGs. The findings of the study reveal the hybrid nature of PMSs within a common institutional context. Originality/value: Drawing on the theoretical frameworks of Bouckaert and Halligan (2007) and Jakobsen et al. (2017), the paper provides an integrated approach for analysing PMSs, considering both objective and subjective dimensions. Insights and indications for future research on hybridity at a meso level of public organizations are highlighted.